Nitrogen Source Regulates Glutamate Dehydrogenase NADP Synthesis in Neurospora crassa - Hernández, Georgina (1983)
Neurospora crassa glutamate dehydrogenase-NADP (EC 1.3.1.3) has a higher activity when mycelium is grown on ammonium or nitrate as nitrogen source than when grown on glutamate or glutamine. Quantitative immunoelectrophoresis established that, under all conditions, enzyme activity corresponded to enzyme concentration. Isotope incorporation studies demonstrated that the nitrogen source exerts its regulation at the level of de novo enzyme synthesis.